2019
DOI: 10.18045/zbefri.2019.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Market concentration and profitability: the empirical evidence from Serbian manufacturing industry

Abstract: The impact of market concentration on profitability is a controversial question in industrial organization without a clear answer. The aim of the research is to investigate this prospective impact in the context of Serbian manufacturing industry. The main hypothesis of the research is that the increase in market concentration increases the profitability in the markets, due to the collusion of the dominant companies. We test this hypothesis by defining, estimating and testing the model describing the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, it was observed that a significant proportion of the market, amounting to 60% in terms of sales revenue and gross value added, is contributed by small enterprises and farms. However, Kastratović et al [30] examined 30,037 financial reports of firms operating in the manufacturing industry sector in Serbia from 2015 to 2017 and concluded that market concentration significantly and positively affects profitability. As far as the research of other countries is concerned, the most comprehensive and up-to-date research was conducted by Grullon et al [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it was observed that a significant proportion of the market, amounting to 60% in terms of sales revenue and gross value added, is contributed by small enterprises and farms. However, Kastratović et al [30] examined 30,037 financial reports of firms operating in the manufacturing industry sector in Serbia from 2015 to 2017 and concluded that market concentration significantly and positively affects profitability. As far as the research of other countries is concerned, the most comprehensive and up-to-date research was conducted by Grullon et al [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concentration reduces the cost of collusion, and market power allows anti‐competitive behavior. Prices are not favorable to the consumer but provide higher profitability to firms (Kastratović et al., 2019). In the same vein, the Relative Market Power hypothesis advocates a positive relationship between concentration and profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Industry capital intensity is generally considered a driver of profitability because firms in the most capital‐intensive industries must invest at a high level to keep their business up and running. Technological advances allow improved productivity and, therefore, profitability is positively affected (Kastratović et al., 2019). Capital intensity could also act as an entry barrier due to two main reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations